2023
DOI: 10.1038/s41598-023-28426-1
|View full text |Cite
|
Sign up to set email alerts
|

Studying the effect of self-selected background music on reading task with eye movements

Abstract: Using background music (BGM) during learning is a common behavior, yet whether BGM can facilitate or hinder learning remains inconclusive and the underlying mechanism is largely an open question. This study aims to elucidate the effect of self-selected BGM on reading task for learners with different characteristics. Particularly, learners’ reading task performance, metacognition, and eye movements were examined, in relation to their personal traits including language proficiency, working memory capacity, music… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…From language and cuisine to architecture and music, regional culture is shaped by a variety of factors, including geography, climate, and historical events. By understanding the connotations of regional culture, we can gain a deeper appreciation for the customs and practices of a particular region and better understand the people who call it home [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From language and cuisine to architecture and music, regional culture is shaped by a variety of factors, including geography, climate, and historical events. By understanding the connotations of regional culture, we can gain a deeper appreciation for the customs and practices of a particular region and better understand the people who call it home [21].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, we can seek out renewable and sustainable sources of resources to reduce our reliance on non-renewable resources. By doing so, we can promote the long-term health and resilience of natural ecosystems while also ensuring that we can continue to meet our resource needs [21].…”
Section: Excavate Social Attribute and Natural Attribute Promote Reso...mentioning
confidence: 99%
“…To assess the PwPT's (patients with psychic trauma) musical aptitudes and perceptual abilities in relation to the sound stimuli to be used for bimodal therapy, we selected the Musical Aptitude and Acoustic Skills test (MAAS [33]). Previous experience with the MAAS test showed that listening to music is preferred in moments of leisure; that "cultured" listening genres (classical, jazz, blues) support serenity and relaxation [34]; that music is perceived as an important aid in improving mood while being a distractor during reading [35]; that melody and rhythm are perceived as fundamental elements of musical communication [36]; that actively seeking out pleasant music is important, while passive reception (subliminal listening, like piped music in shops) is experienced as annoying [37]. The MAAS test was initially applied for training and support purposes in the educational field, a context in which its effectiveness in drawing a picture of acoustic capabilities and musical preferences has been repeatedly validated, with ambisexual learners belonging to various developmental ages [38].…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, the impact of background music (BGM) on cognitive load in learning processes was analyzed through eye movements. It was found that listening to BGM imposed a higher cognitive load on post-lexical processes than on lexical processes [ 22 ]. Eye movement and pupillary response indicators of cognitive load, commonly used in studies, are listed below.…”
Section: Introductionmentioning
confidence: 99%